A rise in accuracy of radio-frequency radiation source coordinates estimation using passive systems with the aid of measuring the rotation period of AFD radar - Ткаченко, В.Н.; Коротков, В.В.; Поздняков, Е.К. (Radiotekhnika, 2012)
The method for determining the range of a radio-frequency radiation source based on the measuring time differences of arrival at the station due to the rotation of the radar’s antenna-feeder device is considered, the required accuracy of the passive location systems temporal parameters is established, mathematical methods for the increase in the range’s definition accuracy are treated.